2016
DOI: 10.1007/8904_2016_6
|View full text |Cite
|
Sign up to set email alerts
|

Very Long-Chain Acyl-Coenzyme A Dehydrogenase Deficiency and Perioperative Management in Adult Patients

Abstract: Surgery and anesthesia pose a threat to patients with very long-chain acyl-CoA dehydrogenase deficiency (VLCADD), because prolonged fasting, stress, and pain are known risk factors for the induction of metabolic derangement. The optimal perioperative management in these patients is unknown and the use of volatile agents and agents dissolved in fatty acids has been related to postoperative metabolic complications. However, the occurrence of metabolic derangement is multifactorial and depends, amongst others, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…Similarly, it has been reported that volatile anesthetics are associated with significant increases in FFA concentrations during the first phases of anesthesia, which in the past has resulted in the development of rhabdomyolysis [ 6 ]. Our results are consistent with the results of recent publications that reported relatively safe volatile agents [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, it has been reported that volatile anesthetics are associated with significant increases in FFA concentrations during the first phases of anesthesia, which in the past has resulted in the development of rhabdomyolysis [ 6 ]. Our results are consistent with the results of recent publications that reported relatively safe volatile agents [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…Propofol includes lipid emulsions; and therefore, it can impair mitochondrial entry of long-chain fatty acids and inhibit the respiratory chain at several points [ 6 , 8 ]. However, there are case reports demonstrating the uneventful use of propofol in individuals with VLCADD and other fatty acid oxidation disorders [ 7 , 19 ]. This makes the use of propofol in patients with VLCADD controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for anesthetics, benzodiazepines, barbiturates, nondepolarizing muscle relaxants, and opioids have been previously used without problems [6,[11][12][13]. Propofol was not selected in the present case because it contains long-chain fatty acids in the solvent [6,13]. There have been conflicting results of using inhaled anesthetics for patients with VLCAD deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Kleemann et al [15] measured plasma concentration of free fatty acids as a marker of catabolism secondary to stress during enflurane anesthesia in patients without VLCAD deficiency and reported that free fatty acids transiently increased around tracheal intubation, but decreased 10 min following the start of enflurane and intraoperatively, suggesting that enflurane anesthesia could suppress stress-induced catabolism [15]. Almost all papers demonstrated that inhaled anesthetics were safely used for patients with VLCAD deficiency [6,13,16]. Iwata et al [16] reported an intraoperative lactate increase in a patient with VLCAD deficiency.…”
Section: Discussionmentioning
confidence: 99%